2015
DOI: 10.1037/xhp0000072
|View full text |Cite
|
Sign up to set email alerts
|

Readers extract character frequency information from nonfixated-target word at long pretarget fixations during Chinese reading.

Abstract: We performed two eye movement studies to explore whether readers can extract character or word frequency information from nonfixated-target words in Chinese reading. In Experiments 1A and 1B, we manipulated the character frequency of the first character in a two-character target word and the word frequency of a two-character target word, respectively. We found that fixation durations on the pre-target words were shorter when the first character of a two-character target word was presented with high frequency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 69 publications
10
23
0
Order By: Relevance
“…(If the output of encoding word n  + 1 is word-based, the reader should have no need to re-encode it when it is in the fixation frame.) Thus, the results of young adults when reading word n  + 1 disappearing text is consistent with the notion proposed by Li and his colleagues who argued that Chinese readers process characters in parallel during reading (Li, Rayner & Cave, 2009; Ma, Li & Rayner, 2015). …”
Section: Discussionsupporting
confidence: 90%
“…(If the output of encoding word n  + 1 is word-based, the reader should have no need to re-encode it when it is in the fixation frame.) Thus, the results of young adults when reading word n  + 1 disappearing text is consistent with the notion proposed by Li and his colleagues who argued that Chinese readers process characters in parallel during reading (Li, Rayner & Cave, 2009; Ma, Li & Rayner, 2015). …”
Section: Discussionsupporting
confidence: 90%
“…In a similar manner, character frequency might also influence the processing of words located in the parafovea. Ma, Li, & Rayner (2015) investigated how the properties of a parafoveal word influence the processing of the currently fixated word (a parafoveal-on-foveal effect); they manipulated both the frequency of the first character of and the whole of a two-character word in the parafovea. They found that the first character frequency-but not the whole word Thus, their results suggest that the characteristics of Chinese characters might be processed in parallel in the parafovea independently of the words they form.…”
Section: N+2 Preview Effectsmentioning
confidence: 99%
“…In contrast, there are few studies using the ex‐Gaussian fitting technique in Chinese reading. In Chinese literature, Ma, Li, and Rayner () performed two experiments to explore whether Chinese readers could extract character or word frequency information from nonfixated‐target words in Chinese reading, and they found Chinese readers could only obtain character frequency information from nonfixated‐target words. Furthermore, they used the ex‐Gaussian fitting technique to fit eye fixation durations on the pretarget region, and the results showed that such parafoveal‐on‐foveal effects (i.e., the properties of a parafoveal word affect how long readers look at the currently fixated word, Kennedy, ) only occurred for long pretarget fixations.…”
mentioning
confidence: 99%
“…Although the ex‐Gaussian function can be well fitted to eye fixation durations in Chinese reading (Ma, Li, & Rayner, ), it is unclear whether word frequency effects, in the distribution level, demonstrate the same way between Chinese and English reading. Even though there are no visual cues marking word boundaries and guiding Chinese readers for saccade‐target selection (Ma, Li, & Pollatsek, ), it is well established that fixation durations were modulated by inserting interword spaces between Chinese words (Bai et al, ; Ma, ).…”
mentioning
confidence: 99%